Determination of antibiotic susceptibility of infectious mastitis of cows and treatment - Abdurasulov Shavkat; Abdusattorov Abdusalom; Amirov Abdumumin (BIO Web of Conferences)
It was found that the overall effectiveness of the drug Mastisan in the treatment of serous, catarrhal, fibrinous, purulent and subclinical mastitis is 80% on average. It was found that the total effectiveness of the Masticide drug in the treatment of serous, catarrhal, fibrinous, purulent and subclinical mastitis is 85%, and milk yield is not completely restored in 14% of cows. Nineteen percent of serous mastitis cows treated with a masticidal drug recover in 10% to 20% of cases with incomplete recovery of milk yield due to pathological changes in the udder teats, while in purulent mastitis 65.60% of cows recover full milk yield, while the remaining 33% of cows recover. full recovery of milk productivity was observed.